STRENGTHENING OF STEELS BY THERMOFRICTION PROCESSING: REVIEW - Yury GUTSALENKO; Cătălin IANCU (Fiabilitate şi Durabilitate)
The presented review is devoted to the method of thermofrictional treatment in terms of its history, successes, problems, current state of development, anticipation of prospects for research and further implementation in practical technology.